A multi-stage approach to support timely health policy decisions during crisis: the fast-track Delphi - Camille Velarde Crézé; Olivier Duperrex; Luc Lebon; Vincent Faivre; Myriam Pasche; Jacques Cornuz (BMC Public Health, 2024)
Abstract Background Scientists can play an important role in policymaking by providing evidence and consensual expert opinion on the state of scientific knowledge. Delphi surveys have been widely used to develop consensus on a topical issue, yet not compatible with public health crisis situations requiring rapid decisions. We developed a fast-track Delphi process, providing experts with a structured approach to rapidly develop and quantify consensus in support of informed policy decisions. Methods We identified key elements of consensus-building techniques through a literature review and derived methodological procedures that served as the basis for the elaboration of the new process. Selected methodological experts provided advice on necessary adjustments. The process was pilot tested using a real-world public health issue. Results The fast-track Delphi process is a hybrid approach between a conventional Delphi and the nominal group technique: one group session followed by two rounds of e-questionnaire, with predefined steps. We developed an ad hoc toolkit (REDCap templates, R code for analysis and production of reports, user guide) to overcome time constraints, which we pilot tested with experts. The feasibility test conducted in 18 days in the field of tobacco control demonstrated the applicability and usefulness of the process in real-world conditions. Conclusions We strongly believe that this fast-track Delphi process has the potential to help inform policy decisions in various types of crises, including emerging diseases or novel potentially harmful products.